The Mekong transport and flood protection project = (The World Bank in Vietnam (WB), 2003)
The closing date for Vietnam, Mekong Transport and Flood Protection Project will be extended from December 31, 2010 until June 30, 2011. The extension for a 6-month period beyond the closing date is necessary to complete on-going activities. The main activities to be supported by the extension are: (i) four (04) on-going works contracts totaling 28km; (ii) two (02) on-going works contracts for black spot improvement; (iii) consultancy services for a feasibility study for future project; and (iv) detailed design consultancy services for remained 30km of roads. This will be the third extension of the original project - Mekong Transport and Flood Protection Project since the original closing date of June 30, 2006 and will be the first extension of the additional financing since the original closing date of December 31, 2010